Effects of Guide Vane Inclination Patterns on Threshing Losses and Power Requirement - Doungpueng, Khunnithi; Chuan-udom, Somchai (Agriculture and Natural Resources, 2014)
A survey and also performance evaluation were undertaken of the guide vane inclination patterns in axial flow threshing units. The study involved two stages: 1) surveying the patterns of the guide vane inclination of rice combine harvesters and 2) studying the effect of the guide vane inclination on the threshing loss and the power requirement. The experiment was performed using the tester threshing unit of the Postharvest Technology Innovation Center, Khon Kaen University. There were three major findings. 1) Guide vane inclination can be adjusted using three patterns—namely, Group 1, where the guide vane inclination of the first 3 blades from the input was smaller than the last 2 blades; Group 2, where the guide vane inclination of all blades on average was similar; and Group 3, where the guide vane inclination of the first and last blades from the input was smaller than the blades at the center of the threshing chamber. 2) The guide vane inclination patterns studied did not have a significant effect on grain breakage, but did on threshing losses and power requirements. 3) The pattern of the guide vane inclination of axial flow rice threshing units for harvesting the Chainat 1 rice variety should be one where the inclination angles consistently increase through 69, 71, 73, 75 and 77 degrees from the threshing axial when the rotor speed is 18 m.s-1 and the feed rate is 16 t.hr-1.